Patient-Centered Care in Primary Care Scale: Pilot Development and Psychometric Assessment. Issue 1 (January 2019) - Radwin, Laurel E.; Cabral, Howard J.; Seibert, Marjorie Nealon; Stolzmann, Kelly; Meterko, Mark; Evans, Leigh; Barker, Anna; Bokhour, Barbara
Abstract : Background: Nurse contributions to patient-centered care in primary care clinics are all but ignored in standard patient experience surveys. Purpose: The purpose was to conduct a pilot study to develop and psychometrically assess a scale measuring nurses' and other providers' patient-centered care in Veteran Affairs primary care clinics. Method: We developed a patient experience survey composed of original items and previous studies' items and scales. The survey was field tested online with patients who had a recent clinic appointment. The nonrandom analytic sample comprised 221 patients. Results: Exploratory factor analyses yielded a 36-item, 4-factor solution explaining 76% of the variance. The factors were: (1) Provider Knowing the Person/Individualizing Care (18 items; α = 0.98); (2) Nurse Knowing the Person (8; 0.95); (3) Nurse Individualizing Care (7; 0.94); and (4) Continuity of Care (3; not calculated). A short form with 23 items was created using stepwise regression. It had the same 4 factors as the long form with 76% of the variance explained. Conclusions: Patients reported distinctive nurse contributions that have not been routinely measured. Abstract : Supplemental Digital Content is Available in the Text.